Using MERSCOPE to Generate a Cell Atlas of the Mouse Brain that Includes Lowly Expressed Genes. (November 2021) - Emanuel, George; He, Jiang
Abstract : Abstract: The structure and organization of cells within organs is essential to their function, but nowhere in the body is this more spectacular than the brain. There, sprawling, snowflake-like neurons have grown into a precise arrangement, reaching out to neighboring cells to form neural circuits. Communication within neural circuits, made possible by spatial positioning, forms the basis of our physiology. Recently, a high-resolution cell atlas generated by MERFISH (multiplex error-robust fluorescence in situ hybridization) technology has mapped this spectacular organ with unmatched resolution, depth, and scale. The atlas catalogs cells as they exist in the intact biological system and will allow us to learn more about rare cell types and sparsely expressed cell signaling receptors fundamental to health and disease.